The Implementation of E-Learning System Governance to Deal with User Need, Institution Objective, and Regulation Compliance - Mujiono Sadikin; Purwanto SK (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
In this digital era, it has been proven that the proper of e-learning system implementation provides various advantages and huge benefits. But to achieve the proper implementation is not an easy way since there are many obstacles have to be addressed. Beside the benefits and advantages, such as the other IT based system, e-learning also bring many risks that come from its environment or embedded in. Although many methods or approaches proposed to tackle those obstacles and risks, but the study that tackle those problems from IT Governance view is still limited. The study presents the report of the IT Governance approach to address some of the risks of eLearning system implementation such as: miss alignment with the enterprise goal and strategies, uncomplianceness with the government regulation, and unmatched with the stakeholder needs. The governance of eLearning system proposed has been implemented in the private university situated in Jakarta, Indonesia for two semesters. Based on the general observation, the University can get some benefits such as their succeed in maintaining its institution as the university that comply with government regulatory.